Pengaruh Consumer Self-Confidence dan Hedonic Shopping Motivations Terhadap Purchase Intention pada Konsumen Produk Skincare Generasi Z di Jayapura - Palti Maretto Caesar Manalu; Neni Setiarini; Iriando Wijaya; El Shaddai Sandhy Pustap; Fanny Kristin Tantyah Sitompul (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to examine the influence of consumer self-confidence and hedonic shopping motivations on the purchase intention of Generation Z toward skincare products in Jayapura. The study employed a quantitative approach using an associative method. Data were collected through questionnaires distributed to 122 Generation Z respondents in Jayapura. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, and f-tests with the assistance of SPSS. The results revealed that consumer self-confidence had a positive and significant effect on purchase intention, with a t-value of 7.294 and a significance level of 0.000. In addition, hedonic shopping motivations also had a positive and significant effect on purchase intention, with a T-value of 2.216 and a significance value of 0.029. Simultaneously, consumer self-confidence and hedonic shopping motivations were proven to significantly influence purchase intention, with an F-value of 112.295 and a significance level of 0.000. The findings indicate that the higher the level of consumer self-confidence and hedonic shopping motivations among Generation Z, the higher their tendency to develop purchase intention toward skincare products.